2007
DOI: 10.1021/es062863j
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing and Biological Monitoring of Polycyclic Aromatic Hydrocarbons in Exposures to Diesel Exhaust

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are one of the most important and carcinogenic components in diesel exhaust (DE). Therefore, ambient PAHs concentrations were measured and characterized for work areas in a locomotive engine inspection plant. Pre- and post-shift urine samples and concurrent air samples were collected on 17 workers to measure the concentration of urinary 1-hydroxypyrene (1-OHP), a metabolite of pyrene. Increased urinary 1-OHP concentrations were observed over at least three consecutive sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 20 publications
1
16
1
Order By: Relevance
“…However, the ambient air concentrations of PAHs in DEP 2.5 in this study were similar to those reported by a study of concentrations at a bus interchange (27.29 ng/m 3 during operating hours and 4.82 ng/m 3 during nonoperating hours) (See et al 2006). One study of a locomotive engine inspection plant revealed that concentrations of PAHs in PM 10 were 1,798 ng/m 3 in the summer and 1,731 ng/m 3 in the winter (Huang et al 2007). Another study performed at a technical diesel revision plant found that concentrations of PAHs in PM 10 were about 30 and 50 ng/m 3 (Adonis et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ambient air concentrations of PAHs in DEP 2.5 in this study were similar to those reported by a study of concentrations at a bus interchange (27.29 ng/m 3 during operating hours and 4.82 ng/m 3 during nonoperating hours) (See et al 2006). One study of a locomotive engine inspection plant revealed that concentrations of PAHs in PM 10 were 1,798 ng/m 3 in the summer and 1,731 ng/m 3 in the winter (Huang et al 2007). Another study performed at a technical diesel revision plant found that concentrations of PAHs in PM 10 were about 30 and 50 ng/m 3 (Adonis et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, occupational research on diesel-related particulate phase PAHs emitted in diesel exhaust mostly focuses on PAHs-absorbed particles less than 10 lm in aerodynamic diameter (PM 10 ) and on PAHs-absorbed particles (Adonis et al 2003;Huang et al 2007;Kuusimäki et al 2002Kuusimäki et al , 2003Seidel et al 2002). Very few studies have analyzed PAHs-absorbed respirable dust and PAHs-absorbed PM 2.5 (See et al 2006;Wheatley and Sadhra 2004).…”
Section: Introductionmentioning
confidence: 99%
“…14 Huang et al studied diesel exhaust exposure in 17 locomotive engine workers, and found the mean t 1/2 was 29 h (6.4-128 h) based on pre and post-shift urine samples over 4 consecutive workdays. 32 In four studies involving 15-20 workers with both inhalation and dermal exposure who provided pre and post-shift samples over 3-5 consecutive days (Table 3), the reported t 1/2 ranged from 5 to 35 hours. [19][20][21]33 In contrast to the consistent half-life estimations from this and existing studies on ingestion exposure, the published results after inhalation and dermal absorption were generally higher and more variable.…”
Section: Excretion Kinetics and Half-life Estimatesmentioning
confidence: 99%
“…Urinary 1-hydroxypyrene (1-OHP), a metabolite of pyrene (21) and one of the components of PAHs in COFs (22), is a possible biological marker of exposure to COFs. Studies have shown that urinary 1-OHP is a good biological marker of exposure to PAHs in fire-fighting workers (23), iron foundry workers (24), and coke oven workers (25,26).…”
Section: Introductionmentioning
confidence: 99%